A Dictionary of Biblical Interpretation - COGGINS, R. J.; HOULDEN, J.L. (London SCM, 1990)
Donated by the Australian College of Theology 1996
Keywords: Bible -- criticism, interpretation, etc; Bible -- dictionaries; Bible -- hermeneutics